2014
DOI: 10.1080/09546553.2014.962989
|View full text |Cite
|
Sign up to set email alerts
|

A Situational Model of Displacement and Diffusion Following the Introduction of Airport Metal Detectors

Abstract: Much of the discourse surrounding counterterrorism centers on the inevitability of displacement, or the substitution of another form of terrorist attack in place of the one that has been thwarted. Yet a longstanding tradition of research in situational crime prevention finds that displacement is far from inevitable, and often depends crucially on the specific features of the incidents in question. In fact, crime prevention efforts are often followed by a ''diffusion of benefits'' (i.e., crime reductions) to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…When faced with counterterrorism measures, prior research suggests that terrorists are induced to alter their targeting strategy. For example, a shift from protected official targets (e.g., government agents) to less defended civilian targets after the deployment of target‐hardening measures (Brandt & Sandler, 2010; Hsu & Apel, 2015; Santifort, Sandler, & Brandt, 2012). Particularly worrisome is the potential for increased bloodshed following government counterterrorism policies.…”
Section: Current Studymentioning
confidence: 99%
“…When faced with counterterrorism measures, prior research suggests that terrorists are induced to alter their targeting strategy. For example, a shift from protected official targets (e.g., government agents) to less defended civilian targets after the deployment of target‐hardening measures (Brandt & Sandler, 2010; Hsu & Apel, 2015; Santifort, Sandler, & Brandt, 2012). Particularly worrisome is the potential for increased bloodshed following government counterterrorism policies.…”
Section: Current Studymentioning
confidence: 99%
“…In this regard, several researchers have also noted the value of using a rational choice perspective in trying to understand and respond to terrorist planning and decision-making, and studies have already identified the rational basis behind terrorist decision-making and how these can identify possible points of intervention to prevent or disrupt effective operations (e.g. Taylor, 1988;Jacobs, 1998;Silke, 2003;Clarke and Newman, 2006;Newman and Hsu, 2012;Hsu and Apel, 2015).…”
mentioning
confidence: 99%
“…While the literature did find that overall hijackings were deterred because of historical situational reforms (Syzliowicz, 2004;Dugan, LaFree, & Piquero, 2005;Clarke & Newman, 2006;Fahey et al, 2011, Hsu & Apel, 2015, Dugan, LaFree, and Piquero (2005) found that terrorists were not as deterred from attempting an attack as offenders who hijack planes for different reasons. This suggests that different situational techniques may need to be utilized to prevent terrorist attacks.…”
Section: Situational Crime Prevention and Terrorismmentioning
confidence: 99%
“…Many of the early situational techniques stem from the reforms implemented in the 1970's (Syzliowicz, 2004;Dugan, LaFree, & Piquero, 2005;Clarke & Newman, 2006;Fahey et al, 2011;Hsu & Apel, 2015). These reforms laid the foundations for future situational prevention techniques in airports.…”
Section: Situational Crime Prevention and Terrorismmentioning
confidence: 99%
See 1 more Smart Citation